2022
DOI: 10.1155/2022/9969158
|View full text |Cite|
|
Sign up to set email alerts
|

The Trend of Burn Injury Patients in Ningbo between 2012 and 2021: A Clinical Study

Abstract: Objective. This study was designed to understand the local changes of burn injuries in recent 10 years, so as to provide reliable reference data and viewpoints for prevention and vigilance of local burn injuries. Methods. In this study, 184 patients with a burn injury admitted to our hospital from 2012 to 2021 were enrolled and analyzed retrospectively. According to their information in the electronic database, the number of patients with burn injuries and the location of each disaster each year were analyzed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%